TINJAUAN YURIDIS KEWAJIBAN DISVESTASI BAGI PERUSAHAAN ASING DALAM PENGELOLAAN PERTAMBANGAN DI INDONESIA - Hudi Karno Sabowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2018)
The mining divestment policy has 3 main key components. First, how much is thedivestment amount. Second, who can buy divested shares. Third, how much is the saleprice of the divested shares. The first element, the divestment requires that everyforeign-owned mining company divest a portion of the increased shares to thegovernment, BUMN or national private sector. (Government Regulation Number 1of 2017, concerning Amendments to Government Regulation Number 23 of 2010,concerning the Implementation of Mineral and Coal Mining Business Activities).The second element, regarding the divestment rules, determines who can buy(Permen ESDM No. 9 of 2017, concerning Procedures for Stock Divestment andMechanism for Determining the Price of Divestment Shares in Minerba MiningBusiness Activities).While the third element is the rule that determines the stock pricewhen it is sold, the share price offered to the Government is determined throughnegotiation. (Government Regulation No. 23 of 2010, concerning theImplementation of Mineral and Coal Mining Business Activities).Industrialdevelopments in the country are still difficult to do, including mining. According toArchandra Tahar, Deputy Minister of Energy and Mineral Resources (ESDM) thereare at least three factors inhibiting the development of the mining sector in Indonesia.These three factors are the problem of banking, technology and political interestrates.